(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Breast carcinoma is one of the most common malignancies among women and remains a major public health concern due to delayed presentation and disease-related morbidity. Early diagnosis, appropriate surgical management, and adjuvant therapy play an important role in improving patient outcomes. Methodology: This hospital-based prospective observational study was conducted among 80 female patients aged 18–65 years with histopathologically confirmed Stage I or II breast carcinoma. Demographic, clinical, reproductive, and treatment-related details were recorded using a structured proforma. Clinical staging was done according to the TNM classification. Patients underwent Modified Radical Mastectomy (MRM) or Breast Conserving Surgery (BCS) as per institutional protocol. Histopathological findings, postoperative complications, and adjuvant therapies were analyzed using IBM SPSS Statistics. Results: The mean age of the study participants was 46.97 ± 10.24 years. Most patients were premenopausal (55.00%), multiparous (78.75%), had Stage II disease (92.50%), positive lymph nodes (80.00%), and invasive ductal carcinoma (90.00%), with the upper outer quadrant (63.75%) being the most common tumor site. MRM (77.50%) was performed more often than BCS (22.50%), mainly due to fear of recurrence (37.50%). Most patients had no postoperative complications, with seroma (7.50%) being the most common. All patients received radiotherapy, while 82.50% received chemotherapy and 63.75% received endocrine therapy. Conclusion: Breast carcinoma commonly affected middle-aged women and frequently presented at Stage II with nodal involvement. Invasive ductal carcinoma was the predominant histological subtype. The findings highlight the importance of early detection, timely surgical intervention, and multimodal adjuvant therapy in improving outcomes among breast carcinoma patients.